Avaliação do potencial de corrosão de armaduras em concretos com substituição parcial do agregado miúdo pela areia de cinza do bagaço da cana-de-açúcar - ACBC - Almeida, Fernando do Couto Rosa (2013)
Brazil is the world's largest producer of sugarcane and the leading exporter of its derivatives (sugar, alcohol, energy etc.). One of the main waste generated in the manufacturing process of this sector is the sugarcane bagasse ash sand (SBAS), produced from the burning of bagasse into boilers to produce electricity (cogeneration). This ash sand is composed of a high amount of silica and it is also currently discarded in cane plantations as organic fertilizer, despite the fact that it is poor in nutrients. This research proposes to provide an alternative application of SBAS in concrete as a replacement material for fine aggregate. Furthermore, the durability of concrete with alternative materials demands a special attention, especially regarding reinforcement corrosion. This is a major concern of the use of wastes on the degradation of concrete structures. The process begins with the despassivation of steel reinforcement, and it propagates in a suitable environment. The aim of this study was to evaluate the potential occurrence of reinforcement corrosion in concrete made with SBAS as a partial replacement material for fine aggregate. The ash sand samples were collected in a plant in the State of São Paulo, and standardized through a sieving and grinding. The SBAS was subjected to physical and chemical characterization, by its chemical composition, sieve analysis, powdery material, absorption, bulk density and true density. Mortars and concretes were produced with levels of substitution of 0% (reference), 30% and 50% of SBAS. In mortars, tests of compressive strength, porosity (void index and pores analysis by optical microscopy), water absorption, accelerated carbonation, chloride penetration and electrical conductivity of the aqueous solution were performed. The concretes were submitted to tests of compressive strength, void index, absorption, chloride penetration, potential and rate of reinforcement corrosion. Thus, the results indicated that substitution of 30% and 50% by SBAS can increase the compressive strength of concrete and the resistance to attack by chlorides, and decrease the despassivation probability of reinforcement. However, with the content of 50% of SBAS, the corrosion rate was significantly higher in comparison to other samples, and it was similar between the concretes with 30% of SBAS and reference. Thus, it was possible to conclude that the concrete with 30% of SBAS as a substitute of fine aggregate may be applied in conventional structural elements without loss of mechanical and durability performance.